The potential of naproxen and its derivatives in inhibiting the processes of initiation, promotion and progression of cancerogenesis - Bednarz, Katarzyna; Banaś, Patryk; Sobańska, Natalia; Banasiak, Aleksandra; Teichman, Rafał; Kasprowicz, Jakub; Pierzchała, Jakub Rafał; Abram, Kamila; Adamus, Justyna; Hyjek, Michał (Journal of Education, Health and Sport, 2022)
Introduction: Naproxen is a non-steroidal anti-inflammatory drug mainly used to treat inflammation, pain, and fever of various etiology. Scientific studies conducted over the last five years have shown, that its introduction significantly influenced neoplastic processes in the in vitro and in vivo studies carried out within cell cultures and animal models. Aim of the study: Our aim was to review the theses, extract and present the influence of naproxen and its derivatives in signaling pathways involved in the initiation, promotion and progression of cancer as well as to indicate potential directions for further research. Methods and materials: We have reviewed the theses in the bibliographic PubMed database, using the keywords: „naproxen”; „naproxen derivatives”; „cancer”; „cancer treatment” „cancer prevention”. Results: In addition to the well-known mechanism of inhibiting COX, there are scientific proofs of the activity of naproxen against other molecules, such as PI3-K (phosphatidylinositol 3-kinase), GSK-3β (glycogen synthase kinase-3β), NFκB (nuclear transcription factor κB), MMP ( metalloproteinases), NO (nitric oxide) involved in neoplastic processes. Conclusion: Conclusions drawn from the analysis of specific molecular activities of naproxen and its derivatives against neoplastic processes are promising. However, more preclinical research is needed to confirm the effectiveness, practical applicability and to assess the side effects of the therapy, before starting the clinical trials in humans.